2011
DOI: 10.1007/s12094-011-0614-0
|View full text |Cite
|
Sign up to set email alerts
|

Correction of systematic set-up error in breast and head and neck irradiation through a no-action level (NAL) protocol

Abstract: NAL off-line protocol is useful for systematic set-up error correction and PTV margin reduction in conventional breast and head and neck irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…10 Lozano reported CTV-PTV margin of 11.8 mm, 14.1 mm and 8.8 mm in the ML, CC and AP directions, respectively. 20 Since the difference in setup errors between a vac fix and routine positioning device is not large and positioning of patients on a vac-fix or alpha cradle either in isolation or in conjunction with a wing/breast board is limited by cost in our country where patients have to bear the expenses, we embarked on the usage of a wing board. A wing board allows relaxation and fixation of arms on a flat board with side wings and a neck support to rest the head and the time required for setup is shorter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Lozano reported CTV-PTV margin of 11.8 mm, 14.1 mm and 8.8 mm in the ML, CC and AP directions, respectively. 20 Since the difference in setup errors between a vac fix and routine positioning device is not large and positioning of patients on a vac-fix or alpha cradle either in isolation or in conjunction with a wing/breast board is limited by cost in our country where patients have to bear the expenses, we embarked on the usage of a wing board. A wing board allows relaxation and fixation of arms on a flat board with side wings and a neck support to rest the head and the time required for setup is shorter.…”
Section: Discussionmentioning
confidence: 99%
“…The CTV to PTV margin derived in our study is comparable to the literature for small breast. 20 An optimal setup image matching position in 2D orthogonal KV images was investigated by Laaksomaa et al 22 Residual errors in the treatment field images were determined by matching the orthogonal setup images to the vertebrae, sternum, ribs and their compromises. The best general image matching position was the compromise of the vertebrae, ribs and sternum and the worst was vertebra alone.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the methodology proposed in the present study does not require the same technical procedures and workload as daily on-line imaging verifications. Indeed, it allows correcting systematic errors and appropriate margin assessment [22][23][24]. We suggest a protocol with a 3 mm action level representing our daily clinical practice because if all the variances are less than 3 mm this typically corresponds to nearly one half of the usual planning risk volume (PRV) margin [20].…”
Section: Limitations and Special Considerationsmentioning
confidence: 99%
“…With Monte Carlo simulations they have shown that to halve the systematic setup error, the NAL protocol only requires 3–5 imaged fractions, while the SAL protocol needs 8–9 imaged fractions. Due to this superiority, the NAL protocol has an extensive application in WBRT with high resulting setup accuracy (6‐8) …”
Section: Introductionmentioning
confidence: 99%